Genetic and clinical profile of high myopia patients with rhegmatogenous retinal detachment - Zhou, Lin; Boboev, Farrukhjon; Chen, Hui; Jiang, Fanwen; Zhang, Chun; Xiao, Jing; Jiang, Hui; Liao, Yongchuan; Xu, Zhuping (Frontiers in Genetics, 2025)
IntroductionOur previous research identified pathogenic variants in RetNet genes in 23.4% of individuals with early-onset high myopia. This study aims to analyze the genetic defects in patients with high myopia complicated by rhegmatogenous retinal detachment.MethodWhole-exome sequencing was performed on 40 patients with high myopia accompanied by retinal detachment. Variants were filtered from 281 RetNet genes, 178 genes related to syndromic high myopia, 23 non-syndromic high myopia-associated genes, and 29 rhegmatogenous retinal detachment-related genes using a multistep bioinformatics approach. Clinical data were collected for genotype-phenotype correlation analysis.ResultsPathogenic variants were detected in 47.5% (19/40) in patients with high myopia accompanied by retinal detachment, specifically in RetNet genes (18/40), rhegmatogenous retinal detachment-related genes (11/40), and syndromic high myopia associated genes (10/40). No variants were found in non-syndromic genes. The most prevalent pathogenic genes for high myopia with retinal detachment were Stickler-related genes, including COL2A1 (10.0%, 4/40) and COL11A1 (5.0%, 2/40). Patients with Stickler-related gene variants presented the youngest average age of retinal detachment onset (35.17 ± 18.03 years) and shortest axial length (27.63 ± 1.01 mm).ConclusionRetNet genes are the predominant causative genes (18/40, 45.0%) in patients with high myopia and retinal detachment. The findings affirm that Stickler syndrome (15%) is a significant etiological factor for high myopia accompanied by retinal detachment. We recommend enhanced comprehensive systemic and ophthalmic examinations for patients with high myopia to enable early detection and prevention of retinal detachment.